Determination of genetic stability of Kelampayan plantlets regenerated from tissue culture using SSR markers - Natalie, anak Gali (Universiti Malaysia Sarawak (UNIMAS), 2012)
Neolamarckia cadamba (Roxb.) Bosser or locally known as Kelampayan is recognized as one of the fast growing forest tree and considered as an industrial species due to its multipurpose and great commercial values as well as possess various medicinal uses. The ability to retain its genetic traits is crucial before micropropagation for largescale commercial production. The objective of this study is to access the genetic stability of Kelampayan plantlets regenerated from tissue culture using SSR markers. In this study, two primers namely NCAC11 and NCAC14 were selected. As a result, the mean number of observed alleles was 2.5 per locus together with 2.247 for the mean effective number of alleles per locus. Besides, the mean for PIC value (Polymorphism information content) was 0.451 and the mean expected heterozygosity was 0.561. The primers NCAC11 and NCAC14 were reported 100% polymorphic. Moreover, a dendrogram constructed using unweighted pair group mean average (UPGMA) and a neighbor-joining tree constructed based on DSA shared allele showed genetic relatedness among the Kelampayan samples. The Kelampayan plantlets regenerated via tissue culture are genetically unstable, due to mislabeling during samples collection or may be during sub-culturing process in the tissue culture laboratory, Sarawak Forest Corporation (SFC), Kuching.